Benefits of Integrating Sustainability into Insurance Companies - Liviu Purcărea; Carmen Valentina Rădulescu; Andreea Maria Mănescu (Revista de Studii Financiare, 2024)
The integration of sustainability in insurance companies has become a priority of the boards and constitutes a strategy in increasing resilience, in terms of improving financial performance and developing innovation. In this article, we will synthesize various studies and perspectives regarding the integration of sustainability in insurance companies, emphasizing both the financial advantages, as well as the operational and reputational ones. In the scientific literature review part, we touched on the research methodologies that highlighted the global sustainability development frameworks. The results obtained suggest that adopting sustainability is essential for long-term success and relevance in a rapidly changing global landscape. Furthermore, the analysis reveals that nearly 50% of the published articles originate from the fields of business, engineering, economics, and social sciences, underscoring the interdisciplinary nature of sustainability research. Future research, as we have seen in studying the activity of BNP PARIBAS CARDIF, should focus on developing comprehensive frameworks for sustainability management in the insurance sector, addressing local and global challenges.